2017
DOI: 10.2172/1365711
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber Manufacturing Facility Siting and Policy Considerations: International Comparison

Abstract: Carbon fiber is a high strength-to-weight ratio material manufactured principally from acrylonitrile, which is increasingly being used in a variety of applications, including recreational products, automobiles, aircraft, wind turbines, and gas pressure vessels. Manufacturing costs can vary between $10 and $25 per kilogram for industrial grades of carbon fiber, and they largely depend on the type and quality of fiber produced (Das et al. 2016). Cumulative demand for carbon fiber has been projected to grow 10% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…PM tools in biomaterials development have been used during project start-up, planning, site selection, and policy establishment of lignin-based carbon fiber production for applications in lightweight vehicles (Cook and Booth, 2017;Das et al, 2016;Yang et al, 2013). (Yang et al, 2013), (2) bottom-up estimation during development, which has been used by researchers in global carbon fiber composites supply chain (Das et al, 2016), (3) economic viability estimation including costs of labor, energy, quality, and regulatory compliance (Cook and Booth, 2017), (4) building and training tools for workforce development programs (Cook and Booth, 2017), and (5) data management tools for project monitoring. These studies suggested that communication channels are better facilitated by co-location and clustering facilities near end users.…”
Section: Biomaterialsmentioning
confidence: 99%
“…PM tools in biomaterials development have been used during project start-up, planning, site selection, and policy establishment of lignin-based carbon fiber production for applications in lightweight vehicles (Cook and Booth, 2017;Das et al, 2016;Yang et al, 2013). (Yang et al, 2013), (2) bottom-up estimation during development, which has been used by researchers in global carbon fiber composites supply chain (Das et al, 2016), (3) economic viability estimation including costs of labor, energy, quality, and regulatory compliance (Cook and Booth, 2017), (4) building and training tools for workforce development programs (Cook and Booth, 2017), and (5) data management tools for project monitoring. These studies suggested that communication channels are better facilitated by co-location and clustering facilities near end users.…”
Section: Biomaterialsmentioning
confidence: 99%
“…While detailed analysis has not been done on the cost of debt for manufacturers to purchase and set up new equipment, or on the high CAPEX needed for setting up a manufacturing facility, it is expected these would be key determinants on manufacturing location. CEMAC has undertaken detailed manufacturing location analysis for other clean energy technologies, such as carbon fiber manufacturing siting, which identified the key role of debt and CAPEX needed in siting new facilities (Cook and Booth 2017). Further analysis will be required to connect potential future growth either in domestic or international SHP markets to potential areas for U.S. SHP manufacturing capacity expansion.…”
Section: Quantitative Factorsmentioning
confidence: 99%
“…Applications of CF currently include high performance automobiles, aircraft sections, wind turbine blades, and gas pressure vessels. Depending on location and sourcing of the precursors and raw materials, the manufactured cost can be $10-$25/kg for industrial grades of CF (Cook and Booth 2017). Figure 14 shows how multiple CF filaments, through precise automation and machinery, can be wound rotationally around symmetrical parts such as shafts, pipes, beams, and vessels/containers (Connova 2017).…”
Section: Composites and Carbon Fiber Benefitsmentioning
confidence: 99%
“…Recently, in Europe, recycling of more than 85% of the CFRPs used in automobiles is an obligatory policy. 18 Therefore, it is necessary to develop an energy-efficient recycling technology in order to expand the CFRP markets. Additionally, the price of CF yarn is about $30/kg, and the energy required for manufacturing is about 150−300 kWh/ kg.…”
Section: Introductionmentioning
confidence: 99%
“…Sending conventional CFRPs to landfill should be avoided for both environmental and economic aspects. Recently, in Europe, recycling of more than 85% of the CFRPs used in automobiles is an obligatory policy . Therefore, it is necessary to develop an energy-efficient recycling technology in order to expand the CFRP markets.…”
Section: Introductionmentioning
confidence: 99%